2008
DOI: 10.1186/1477-7827-6-24
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmunity in gestational diabetes mellitus in Sardinia: a preliminary case-control report

Abstract: These results are in contrast with the very low prevalence of all antibodies reported in Italy. If confirmed, they could indicate that a large proportion of GDM patients in Sardinia have an autoimmune origin, in accordance with the high prevalence of Type 1 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Women with autoimmune GDM have been earlier shown to have lower BMI, lower waist circumference, less weight gain during pregnancy, and lower fasting insulin levels compared to women with nonautoimmune gestational diabetes. [ 21 22 ] These parameters might help to identify a subset of women with GDM who are likely to progress to T1DM postpartum; however, these findings need to be evaluated by larger prospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…Women with autoimmune GDM have been earlier shown to have lower BMI, lower waist circumference, less weight gain during pregnancy, and lower fasting insulin levels compared to women with nonautoimmune gestational diabetes. [ 21 22 ] These parameters might help to identify a subset of women with GDM who are likely to progress to T1DM postpartum; however, these findings need to be evaluated by larger prospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…About 10% of all GDM women develop T2D after delivery. Though pancreatic autoimmunity does not seem to represent a typical marker of GDM [ 21 ], high prevalence of autoantibodies, such as anti-GAD65 and anti-IA2 antibodies, has been observed in GDM subjects [ 22 ]. Maternal transmission of these autoantibodies did not affect diabetic risk in the offspring.…”
Section: Cell-mediated Immunity In Diabetic Pregnancy and Macrosommentioning
confidence: 99%
“…The prevalence of autoantibodies in GDM has been assessed in several small studies. The prevalence of glutamic acid decarboxylase (GAD) varies from 0-11 %, tyrosine-phosphatase-like islet antigen (IA-2) from 0-6 %, islet cell antibodies (ICA) from 1-15 %, and anti-insulin autoantibodies (IAA) from 0-6 % [41][42][43][44]. Antibodies to a zinc transporter (ZnT8) have not yet been reported in GDM.…”
Section: Islet Autoimmunity In Gdm: Prevalence Trajectory and Clinicmentioning
confidence: 99%
“…With regard to future diabetes risk, the presence and number of positive diabetes-related autoantibodies in GDM have been associated with an increased risk of type *Different to Anglo-Celtiĉ Large for gestational age 1 diabetes in populations with a high background risk, such as Finland and Sardinia [43,49]. A study of 385 Swedish women with GDM found that 24 women (6 %) had one antibody positive [42].…”
Section: Islet Autoimmunity In Gdm: Prevalence Trajectory and Clinicmentioning
confidence: 99%